PORTRAYAL OF TRANSGENDER ON FACEBOOK AND AUDIENCE BEHAVIOR: A CASE STUDY OF JULIE KHAN - Dr. Saima Waheed (Journal of Peace, Development and Communication, 2022)
This study examines the portrayal of transgender on Facebook by The centrum Media (TCM) Originals that had made a series namely Naked Truth in which they had featured Julie Khan (Transgender). Various national and international studies have been reviewed in this research. Agenda setting theory has been applied in this study. Content analysis has been selected with a systematic random sampling technique. Two units are segmented in this study for analysis. One was the dialogues of Julie Khan, and the second one was Audience comments on the videos of Julie khan, which TCM uploaded on the platform of Facebook. Season 01 has been selected as the population of the study. In these videos, Julie Khan highlighted different kind of issues in Pakistan. The conclusion was in favor of Julie Khan. People highly encouraged the videos and issues discussed by Julie Khan in the series Naked Truth.